Pharmacologic TWIK‐related acid‐sensitive K+ channel (TASK‐1) potassium channel Inhibitor A293 facilitates acute cardioversion of paroxysmal atrial fibrillation in a porcine large animal model - Wiedmann, Felix Tobias; Beyersdorf, Christoph; Zhou, Xiao-Bo; Büscher, Antonius; Kraft, Manuel; Nietfeld, Jendrik; Puig Walz, Teo; Unger, Laura Anna; Loewe, Axel; Schmack, Bastian; Ruhparwar, Arjang; Karck, Matthias; et al. (Journal of the American Heart Association, 2020)
BackgroundThe tandem of P domains in a weak inward rectifying K+ channel (TWIK)‐related acid‐sensitive K+ channel (TASK‐1; hK2P3.1) two‐pore-domain potassium channel was recently shown to regulate the atrial action potential duration. In the human heart, TASK‐1 channels are specifically expressed in the atria. Furthermore, upregulation of atrial TASK‐1 currents was described in patients suffering from atrial fibrillation (AF). We therefore hypothesized that TASK‐1 channels represent an ideal target for antiarrhythmic therapy of AF. In the present study, we tested the antiarrhythmic effects of the high‐affinity TASK‐1 inhibitor A293 on cardioversion in a porcine model of paroxysmal AF.Methods and ResultsHeterologously expressed human and porcine TASK‐1 channels are blocked by A293 to a similar extent. Patch clamp measurements from isolated human and porcine atrial cardiomyocytes showed comparable TASK‐1 currents. Computational modeling was used to investigate the conditions under which A293 would be antiarrhythmic. German landrace pigs underwent electrophysiological studies under general anesthesia. Paroxysmal AF was induced by right atrial burst stimulation. After induction of AF episodes, intravenous administration of A293 restored sinus rhythm within cardioversion times of 177±63 seconds. Intravenous administration of A293 resulted in significant prolongation of the atrial effective refractory period, measured at cycle lengths of 300, 400 and 500 ms, whereas the surface ECG parameters and the ventricular effective refractory period lengths remained unchanged.ConclusionsPharmacological inhibition of atrial TASK‐1 currents exerts antiarrhythmic effects in vivo as well as in silico, resulting in acute cardioversion of paroxysmal AF. Taken together, these experiments indicate the therapeutic potential of A293 for AF treatment.
Im Titel ist "+" in K+ hochgestellt
Gesehen am 03.09.2020